Son-Condescension and the Logic of Theology - Shannon, Nathan D. (2017)
In the following essay, I compare concrete and abstract theological logics, critiquing the latter in favor of a biblical-revelational version of the former. I then move the comparison to the specific issue of biblical interpretation. Abstraction bares its antinomies openly here. The biblical-revelational approach focuses on Son-condescension as the mode of God’s every act with regard to not-God. If Son-condescension is the mode of the Creature/creature relation, then it should also be the logic of understanding it. Therefore, I commend a Son-condescension model for explaining the Creator/creature relation and then more basically as the logic of Christian theism.
In dem folgenden Aufsatz vergleiche ich konkrete und abstrakte theologische Logik, wobei ich letztere kritisch betrachte zugunsten einer biblisch-offenbarenden Version der ersteren. Dann gehe ich mit dem Vergleich weiter zu der spezifischen Frage der biblischen Interpretation. Die Abstraktion legt hier klar ihre Antimonien bloß. Der biblisch-offenbarende Ansatz richtet seinen Fokus auf die Menschwerdung des Sohnes als Modus für jegliches Handeln Gottes in Bezug auf das, was nicht Gott ist. Wenn die Menschwerdung des Sohnes der Modus der Beziehung Schöpfer/Geschöpf ist, dann sollte das auch die Logik sein, mit der man dieses versteht. Daher empfehle ich das Model der Menschwerdung des Sohnes zur Erklärung der Beziehung Schöpfer/Geschöpf und dieses dann grundlegender als Logik des christlichen Theismus.
Keywords: Theological Method -- theological predication -- doctrine of God -- Christology -- theology and logic; theologische Methode -- theologische Prädikation -- die Lehre von Gott -- Christologie -- Theologie und Logik